2010
DOI: 10.3102/0002831210374351
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Pathways Through Four-Year Colleges

Abstract: Pathways through college vary by sex in ways that may contribute to the contemporary male-female gap in college graduation that favors women. Although past research has documented sex differences in college pathways, little research has investigated the underlying causes of this variation. Using data from the National Education Longitudinal Study, this study empirically tests leading hypotheses for why men are more likely than women to progress through college discontinuously and part-time. This study finds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…The finding that age 7 and age 21 reading or math skills were not significant predictors of college completion in this sample suggests that acquiring a college degree requires more than performing well on reading and math assessments. This was somewhat surprising because previous research has found that college grades and achievement significantly predict college completion (Buchmann & DiPrete, 2006; Ewert, 2010; Velez, 1985). The difference in results could be due to measurement because other studies finding significant effects of college grades completion have examined grades and GPA rather than standardized achievement tests (Buchmann & DiPrete, 2006; Velez, 1985).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The finding that age 7 and age 21 reading or math skills were not significant predictors of college completion in this sample suggests that acquiring a college degree requires more than performing well on reading and math assessments. This was somewhat surprising because previous research has found that college grades and achievement significantly predict college completion (Buchmann & DiPrete, 2006; Ewert, 2010; Velez, 1985). The difference in results could be due to measurement because other studies finding significant effects of college grades completion have examined grades and GPA rather than standardized achievement tests (Buchmann & DiPrete, 2006; Velez, 1985).…”
Section: Discussionmentioning
confidence: 89%
“…This is based on research finding that college achievement levels significantly predict college completion (Buchmann & DiPrete, 2006; Ewert, 2010; Velez, 1985). Thus, it is possible that children’s early attention span-persistence is related to stronger reading and math levels later in an individual’s academic career (age 21), which would then be related to greater odds of completing college by age 25.…”
Section: Relations Between Preschool Attention Span-persistence and Amentioning
confidence: 99%
“…Because past research shows that men and women often react differently in the school context(Cai 2005;Else-Quest et al 2010;Ewert 2010;Fan 2011;Tison et al 2011), we replicated our final model while…”
mentioning
confidence: 81%
“…Older students stop out at higher rates because they tend to have more family and work commitments than do younger students (Pascarella and Terenzini 2005). Men are also more likely than women to take breaks from school, largely because of their relatively poorer academic performance in both high school and college (Ewert 2010). Some studies also demonstrate racial differences in students' persistence in college (Goldrick-Rab 2006; Moore and Shulock 2010); this might be expected because racial inequality and discrimination continue to negatively impact educational opportunities for Black and Latino students (Kasinitz et al 2008).…”
Section: The Problem Of Poor Student Retention and Degree Completion mentioning
confidence: 99%